Berberine augments the secretory function of salivary gland in homeostasis and after radiation exposure - Lian, Qihang; Tian, Yue; Wang, Nan; Luo, Yikun; Wang, Xi; Liu, Banghui; Tian, Hefei; Liu, Xiangjun; Yin, Qingping; Xu, Zhenni; Huang, Yujun; Huang, Lingxiao; et al. (Frontiers in Immunology, 2026)
IntroductionRadiotherapy serves as an essential therapeutic modality for head and neck malignancies. However, many patients who undergo head and neck radiation (HNR) frequently experience different severities of xerostomia. Berberine (BBR) has a variety of pharmacological functions and has shown favorable clinical efficacy. However, its therapeutic potential and mechanistic basis in xerostomia have not been explored.MethodsThe histological expressions of Aquaporin 5 (AQP5), Na-K-Cl cotransporter 1 (NKCC1), Muscle intestine stomach expression 1 (MIST1), Proliferating cell nuclear antigen (PCNA), Phospho-GSK-3beta (p-GSK3β) and β-Catenin were examined by immunohistochemistry (IHC). Mucin2 (MUC2), were examined by immunofluorescence. The degree of apoptosis was assessed by TUNEL. The mRNA expression levels of AQP5, NKCC1, PCNA, MUC2, and MIST1 were detected by qRT-PCR assay. The degree of inflammatory was evaluated by detecting the mRNA expression levels of Il1b, Tgfb1, Tnf, and Il10. The Proliferation level was performed by salivary gland organoids.ResultsBBR significantly enhanced saliva secretion in normal physiological conditions and after radiation injury. Mechanistically, BBR upregulated the expression of AQP5, NKCC1 and MIST1. Moreover, BBR conferred its protection via the upregulation of mucin 2 (MUC2) expression, and qPCR analysis revealed elevated Bhlha15 levels. Additionally, BBR preserved cellular proliferation, decreased TUNEL+ apoptotic cells and the inflammatory response in SMG tissues and organoids in HNR-induced xerostomia models.ConclusionIn conclusion, this study demonstrates that BBR can increase saliva secretion in healthy and HNR mice, indicating its potentiality for the treatment of radiation-induced xerostomia.